Back-End Geographic Information System Development for Linguistic and Literary Mapping in Jambi Province - Cagivamito Tadashi Hutabarat; Pradita Eko Prasetyo Utomo; Ulfa Khaira (Brilliance: Research of Artificial Intelligence, 2025)
Indonesia possesses a rich diversity of regional languages and literature, including 718 recorded languages and 965 literary works nationally. Jambi Province, with its seven local languages and abundant oral traditions, requires more effective preservation efforts. Currently, available information is limited to static physical maps that are difficult to access. This study aims to develop a web-based Geographic Information System to digitally, interactively, and flexibly map the distribution of languages, literature, and scripts in Jambi. The system was developed using the System Development Life Cycle (SDLC) approach with an Incremental model, allowing for gradual development and continuous adjustments. The primary focus was on back-end development, including the database, business logic, and server. Functional testing was conducted using black-box testing, while non-functional performance evaluation was carried out through load testing using k6 on the main features, simulating 50 Virtual Users (VUs). Test results indicated that the system was stable and responsive, with a 0.00% failure rate, average response times of 59.08–68.74 ms, and a P95 not exceeding 106 ms. The system was developed in two increments: a general user interface and an administrator dashboard, enabling efficient management of language, literature, script, announcement, and feedback data. The implementation of this digital platform enhances information accessibility, supports the Language Office of Jambi Province in data dissemination, and contributes to the preservation of regional cultural heritage for the public and researchers.